2019
DOI: 10.4300/jgme-d-19-00386.1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Residents With Progress Issues Using a Keyword–Specific Algorithm

Abstract: Background The literature suggests that specific keywords included in summative rotation assessments might be an early indicator of abnormal progress or failure. Objective This study aims to determine the possible relationship between specific keywords on in-training evaluation reports (ITERs) and subsequent abnormal progress or failure. The goal is to create a functional algorithm to identify residents at risk of failure. Methods A database of all ITERs from all residents training in accredited programs at Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In this capacity, it would be valuable to utilize keyword technology and machine learning algorithms to identify trends to facilitate earlier interventions among "at-risk" learners. 33,65 More recently (and outside of our present study period), a conversation has begun in the literature that describes the nature of dashboards that marshal these types of real-time data flows. 19,66 Exciting new areas of research that have more recently shown up in the literature (both within and outside of EM) include the incorporation of EHR data for trending or tracking workplace outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this capacity, it would be valuable to utilize keyword technology and machine learning algorithms to identify trends to facilitate earlier interventions among "at-risk" learners. 33,65 More recently (and outside of our present study period), a conversation has begun in the literature that describes the nature of dashboards that marshal these types of real-time data flows. 19,66 Exciting new areas of research that have more recently shown up in the literature (both within and outside of EM) include the incorporation of EHR data for trending or tracking workplace outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Data should be aggregated and presented in a manner to augment decision making or trainee support in a meaningful format. In this capacity, it would be valuable to utilize keyword technology and machine learning algorithms to identify trends to facilitate earlier interventions among “at‐risk” learners 33,65 . More recently (and outside of our present study period), a conversation has begun in the literature that describes the nature of dashboards that marshal these types of real‐time data flows 19,66 .…”
Section: Discussionmentioning
confidence: 99%
“…Estimates suggest anywhere from 5 to 10% of residents "struggle" during their training, with many problems identified too late to maximize help to the learner [14][15][16][17]. Multiple studies have shown the value of narrative data in making summative decisions, while others have attempted to predict ongoing struggles with learner development [12,[18][19][20]. However, challenges exist when using narrative data in these ways.…”
Section: Introductionmentioning
confidence: 99%
“…Carefully collected and analyzed narrative assessment data can provide value, particularly early in training given their potential to capture rich details about a learner’s performance. Different approaches to finding value in narrative data have included the use of “keyword algorithms” or counting the number of words and percentage of assessments containing negative or ambiguous comments, which were associated with the need for remediation [ 15 , 19 ]. However, using keyword algorithms was much better at ruling out, rather than predicting who would struggle as evidenced by a positive predictive value of 23% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation